Manufacturing technology selection: a supply chain perspective - Farooq, Sami (2007)
This thesis describes a technology selection framework for manufacturing technology selection. Technology selection has been identified as a major area of decision making in a company's manufacturing strategy and is highlighted as a manufacturing objective that can provide competitive advantage to a company. The research identifies the emergence of global supply chains as a major phenomenon that has revolutionised the global business environment. Considering the presence of global supply chains and their ever increasing importance the research has proposed a process for manufacturing technology selection keeping in view the supply chain perspective. The technology selection framework introduces the concept of risk evaluation of available technology alternatives for strategic technology selection. The risk associated with technology alternatives is evaluated in the shape of opportunities and threats. The decision making environment for technology selection is divided in a way to consider intra as well as inter-organisational factors. The classification of the decision making environment, inclusion of risk calculations and consideration of a supply chain perspective enables the developed technology selection framework to thoroughly evaluate a technology alternative before its strategic selection. The research presented in this thesis is composed of two main sections. The first section deals with the development of the technology selection framework, whereas the second section describes the application of the developed framework in an aerospace manufacturing company in detail. The application of the framework in industry helped in understanding the issues surrounding the technology selection process and provided an insight into how the existing technology selection processes can be improved and why it is necessary to address the supply chain factors functionally as well as holistically in manufacturing technology selection. The major contribution of this research is a technology selection framework integrating manufacturing and the supply chain. Academically the research establishes a link between manufacturing technology selection and the supply chain and emphasises the importance of alignment between manufacturing and supply chain objectives.